The Symmetry of Neural Stem Cell and Progenitor Divisions in the Vertebrate Brain - Casas Gimeno, Glòria; Paridaen, Judith T. M. L. (Frontiers in Cell and Developmental Biology, 2022)
Robust brain development requires the tight coordination between tissue growth, neuronal differentiation and stem cell maintenance. To achieve this, neural stem cells need to balance symmetric proliferative and terminal divisions with asymmetric divisions. In recent years, the unequal distribution of certain cellular components in mitosis has emerged as a key mechanism to regulate the symmetry of division, and the determination of equal and unequal sister cell fates. Examples of such components include polarity proteins, signaling components, and cellular structures such as endosomes and centrosomes. In several types of neural stem cells, these factors show specific patterns of inheritance that correlate to specific cell fates, albeit the underlying mechanism and the potential causal relationship is not always understood. Here, we review these examples of cellular neural stem and progenitor cell asymmetries and will discuss how they fit into our current understanding of neural stem cell function in neurogenesis in developing and adult brains. We will focus mainly on the vertebrate brain, though we will incorporate relevant examples from invertebrate organisms as well. In particular, we will highlight recent advances in our understanding of the complexities related cellular asymmetries in determining division mode outcomes, and how these mechanisms are spatiotemporally regulated to match the different needs for proliferation and differentiation as the brain forms.